The Role of the Economic Security Strategy in the Activity of Enterprises and the Principles of Its Work - Khaitov O. N.; Boynazarova N. B. (Research Parks Publishing LLC, 2023)
In the article, the author's enterprise is to help with issues related to the processes of economic activity and to control the economic situation. The positive aspects of the development of economic profit strategy have been tried to a good result. Problems and solutions related to economic problems are explained.